Money and price dynamics under the gold standard in the neoclassical theory of growth - Wei-Bin Zhang (Lecturas de Economía, 2019)
The purpose of this study is to determine money and price dynamics under the gold standard in the one-sector neoclassical growth model. To do this, a model is built upon a few approaches in the literature on dynamic economic theory. In particular, the production sector is based on the Solow model, the gold standard and price dynamics are founded on Barro (1979), and money demand is influenced by the traditional money-in-the-utility-function setup. The model integrates the ideas of these approaches within a compact framework. Through simulations, it is shown that the economic system is characterized by a unique unstable steady state. Also, comparative dynamic analyses regarding changes in some parameters are conducted.